Case Study of 250 ML Glass Drinking Water Product Defects with Lean Six Sigma and FMEA - Rosyidi, Moh Ririn; Izzah, Nailul; Narto, Narto (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
The quality of this product/service is critical because it is a component of consumer needs that provides an assessment of the product that has been purchased; consumers will buy the product again if the quality matches existing specifications; and consumers will indirectly recommend it to other consumers who will purchase it. The same product of established quality. Clue for business actors: product/service quality is essential for a company's survival; ongoing quality improvement measures in response to competition that can match product quality; and minimizing faults in the manufacturing process. PT. XYZ, the findings of this study will help to reduce waste (defects) by recognizing, understanding, and managing the quality of drinking water glass products in a measured and systematic way. The results show that there is a lot of waste that occurs in product faults (27), and it can be noted that activities have a VA value of 11%, NNV 64%, NVA 11%, and a sigma value of 3, dpmo 12,256 in 250ml bottled glass drinking water goods. There is a need for repairs and control, material inspection prior to the process, regular operator training, warning operators not to make mistakes, replacing or replacing machine units that are no longer suitable, and providing clearer work procedures to resolve defects and waste problems.